Catching invasive Chinese mitten crabs while releasing the endangered European eel and other fish by‐catch: The implications of fyke net design. Issue 6 (29th June 2017) - Clark, Paul F.; Stefanoudis, Paris V.; Crimmen, Oliver A.; Pearce, Dave; Clifton‐Dey, Darryl; Morritt, David
Abstract: Modifications of a traditional fyke net design were trialled in 42 hauls over 5 months at 42 locations in the Thames estuary, London. These trials were to determine whether the modified nets could be used to catch invasive mitten crabs while at the same time releasing endangered eels, back into the river. The modifications included rings of different diameters fixed into the netting to provide escape apertures and also a variation in mesh size. A standard, unmodified net was included as a control. Captured mitten crabs, eels and other fish by‐catch were measured and recorded for all deployed nets. Mitten crabs and eels were caught in all nets except those of the largest mesh size (70 mm) which caught no eels. This may have been the combined effect of the mesh size and it being set on the square, versus the normal diagonal netting which may become increasingly constricted in one axis, under tension. Such a square mesh net could be used to trap crabs of carapace width > 65 mm, while releasing all eels. The smallest rings, 22 mm internal diameter, inserted into the mesh may have allowed the escape of eels < 35 cm length, but retained larger, market legal, individuals. This suggests that a slightly smaller escape ring could potentially be used to release eels of ≤ 30 cm in length, in line with current regulations.